2010
DOI: 10.1021/jo100826e
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Mutarotation of 1-Thioaldoses in Water. Unexpected Behavior of (2S)-d-Aldopyranoses

Abstract: The pH-dependent mutarotation of 1-thioaldopyranoses in aqueous media has been investigated. Anomerization readily occurred at lower and neutral pH for all aldopyranoses studied, whereas mainly for (2S)-D-aldopyranoses at higher pH. 1-Thio-D-mannopyranose and 1-thio-D-altropyranose showed very strong pH dependence where the anomeric equilibrium ratios changed dramatically from a preference for the β-anomer at lower pH to the α-anomer at higher pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 51 publications
1
28
0
2
Order By: Relevance
“…Thus, ring opening and subsequent mutarotation of 1-thiosaccharides are hindered. Nevertheless, it has recently been demonstrated that anomerization readily occurs for a range of 1-thiosaccharides in aqueous solution in a pH-dependent process [66]. In the present case, the NMR analyses similarly revealed the formation of the β-anomer in the product mixture.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Thus, ring opening and subsequent mutarotation of 1-thiosaccharides are hindered. Nevertheless, it has recently been demonstrated that anomerization readily occurs for a range of 1-thiosaccharides in aqueous solution in a pH-dependent process [66]. In the present case, the NMR analyses similarly revealed the formation of the β-anomer in the product mixture.…”
Section: Resultssupporting
confidence: 52%
“…As reported, the mutarotation of 1-glycosyl thiols is pH-dependent [66], and the reaction is generally impaired under basic conditions. To test the effect from added base in the present study, the tosyl electrophile, which originally led to a mixture of anomeric products at 50 °C in DMF, was subjected to glycosylation using 1-thio-α- d -mannopyranose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent in-depth study on the mutarotation of 1-thio-aldoses in aqueous media has shown that anomerization of certain 1-thiosaccharides readily occurs at different pH in aqueous media. 55 Ring opening and exocyclic cleavage were found to account for the conspicuous mutarotations.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we are particularly interested in the direct palladium‐catalyzed coupling of unprotected glycosyl thiols under mild and operationally simple conditions. Catalytic reactions of this nature would be of great interest for the construction of molecules that may be sensitive to the harsh conditions that can often be required for thioglycosidic4 bond‐forming reactions 5. In 2013, our group reported the coupling of protected glycosyl thiols with aryl halides in the presence of Pd(OAc) 2 /XantPhos as the catalytic system, NEt 3 as the base in dioxane at 100 °C (Scheme , path a) 6.…”
Section: Methodsmentioning
confidence: 99%